CRISPR Chronicles: Advancing Gene Editing in Cardiovascular Treatment - Sahlan Abdullah Rohim (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
CRISPR-Cas technologies have transformed gene editing, providing accurate and effective genome alterations with extensive implications in biological research and treatment strategies. This technology has eclipsed conventional techniques, including zinc-finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs), owing to its simplicity, cost-efficiency, and superior precision. In cardiovascular disease (CVD) research, CRISPR has been essential in creating accurate disease models, pinpointing genetic risk factors, and formulating possible therapeutic approaches. Genome editing has facilitated the rectification of monogenic mutations associated with inherited cardiomyopathies and arrhythmias while also addressing metabolic risk factors like PCSK9 to mitigate atherosclerosis. Innovations including base editing, prime editing, and RNA editing have augmented CRISPR's accuracy, reducing off-target effects and enhancing therapeutic relevance. Delivery modalities, encompassing adeno-associated viral (AAV) vectors and nanoparticle-based approaches, have been refined to improve efficacy and safety. Notwithstanding these advancements, difficulties, including inadvertent genetic alterations, immunological reactions, and ethical dilemmas surrounding germline editing, remain. The effective clinical implementation of CRISPR therapeutics necessitates additional refinement, stringent validation, and regulatory supervision to guarantee safety and efficacy. Ongoing research indicates that CRISPR-based genome editing possesses significant advantages for improving cardiovascular treatment. Advancements in delivery methods, enhanced precision in gene editing, and ethical considerations will be pivotal in the incorporation of CRISPR into clinical practice. Through ongoing advancement, CRISPR possesses the capacity to emerge as a revolutionary therapeutic instrument, providing accurate and enduring remedies for cardiovascular diseases and many genetic problems